Population in the 1990s - United Nations (Asia-Pacific Population Journal, 1989)
Developments in the field of population in the Asian and Pacific region have passed through three distinct evolutionary stages over the last three decades. The 1960s was a period of awareness of population problems and development of experimental family planning programmes to counteract the rapid population growth apparent in many countries. The 1970s witnessed further development in national family planning programmes as a result of the adoption of population policies to curb population growth and to solve other related problems.